18.8k views
0 votes
Determine the inverse of the following function and explain the process you used to find it. f(x)=3x+1

Determine the inverse of the following function and explain the process you used to-example-1
User Ziko
by
5.4k points

1 Answer

2 votes

To find the inverse we write the function as:


y=3x+1

Now we interchange the name of the variable, that is:


x=3y+1

Now we solve the equation for y:


\begin{gathered} x=3y+1 \\ 3y=x-1 \\ y=(x-1)/(3) \end{gathered}

Therefore the inverse functioni is:


f^(-1)(x)=(x-1)/(3)

User Jonathan Eunice
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.